Three dimensional extrusion printing induces polymer molecule alignment and cell organization within engineered cartilage. Issue 8 (30th April 2018) - Guo, Ting; Ringel, Julia P.; Lim, Casey G.; Bracaglia, Laura G.; Noshin, Maeesha; Baker, Hannah B.; Powell, Douglas A.; Fisher, John P.
Abstract: Proper cell–material interactions are critical to remain cell function and thus successful tissue regeneration. Many fabrication processes have been developed to create microenvironments to control cell attachment and organization on a three‐dimensional (3D) scaffold. However, these approaches often involve heavy engineering and only the surface layer can be patterned. We found that 3D extrusion based printing at high temperature and pressure will result an aligned effect on the polymer molecules, and this molecular arrangement will further induce the cell alignment and different differentiation capacities. In particular, articular cartilage tissue is known to have zonal collagen fiber and cell orientation to support different functions, where collagen fibers and chondrocytes align parallel, randomly, and perpendicular, respectively, to the surface of the joint. Therefore, cell alignment was evaluated in a cartilage model in this study. We used small angle X‐ray scattering analysis to substantiate the polymer molecule alignment phenomenon. The cellular response was evaluated both in vitro and in vivo . Seeded mesenchymal stem cells (MSCs) showed different morphology and orientation on scaffolds, as a combined result of polymer molecule alignment and printed scaffold patterns. Gene expression results showed improved superficial zonal chondrogenic marker expression in parallel‐aligned group. The cell alignment was successfully maintained in the animal model after 7 days with distinct MSC morphology between the casted and parallel printed scaffolds. This 3D printing induced polymer and cell alignment will have a significant impact on developing scaffold with controlled cell–material interactions for complex tissue engineering while avoiding complicated surface treatment, and therefore provides new concept for effective tissue repairing in future clinical applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2190‐2199, 2018.